2016
DOI: 10.1038/ncomms13287
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA GAS5 controls human embryonic stem cell self-renewal by maintaining NODAL signalling

Abstract: Long non-coding RNAs (lncRNAs) are known players in the regulatory circuitry of the self-renewal in human embryonic stem cells (hESCs). However, most hESC-specific lncRNAs remain uncharacterized. Here we demonstrate that growth-arrest-specific transcript 5 (GAS5), a known tumour suppressor and growth arrest-related lncRNA, is highly expressed and directly regulated by pluripotency factors OCT4 and SOX2 in hESCs. Phenotypic analysis shows that GAS5 knockdown significantly impairs hESC self-renewal, but its over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
99
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 63 publications
2
99
0
1
Order By: Relevance
“…Among the enriched pathways, we focused our analysis on the G1‐S cell cycle phase transition, because this is known to play a major role in ESC stemness . Moreover, there are few reports on the involvement of lncRNAs in cell cycle regulations of hESCs …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the enriched pathways, we focused our analysis on the G1‐S cell cycle phase transition, because this is known to play a major role in ESC stemness . Moreover, there are few reports on the involvement of lncRNAs in cell cycle regulations of hESCs …”
Section: Resultsmentioning
confidence: 99%
“…Lin et al showed that Tcl1 upstream neuron‐associated lincRNA, or megamind (TUNA) plays a vital role in pluripotency of mouse ESCs by regulating the expressions of core pluripotent TFs (SOX2 and NANOG) which was further supported by Jacobs et al Another lncRNA, Linc‐ROR was reported to function as a competing endogenous RNA (ceRNA) and promote the expressions of 3 core pluripotent TFs, OCT4, SOX2, and NANOG, via interacting with hsa‐miR‐145‐5p to regulate self‐renewal of hESCs . Gas5, a growth arrest‐related lncRNA, was also seen to control self‐renewal of hESCs, which is directly regulated by OCT4 and SOX2 . Further, studies have shown that lncRNAs play important roles in regulating hESC‐specific transcriptional activation of genes by controlling posttranscriptional regulations by acting as miRNA sponge or by facilitating epigenetic modification via contributing to the functioning of chromatin modifiers .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…In addition, several signaling pathways have been shown to play important roles in controlling self‐renewal of SSCs, including MEK–ERK, PI3K–Akt, Wnt–β‐catenin, and JAK–STAT signaling (Golestaneh et al, ; Hasegawa, Namekawa, & Saga, ; J. Lee et al, ; Tulina & Matunis, ). In recent years, regulatory noncoding RNAs (ncRNAs), such as microRNA (miRNA), long ncRNA (lncRNA), piwi‐interacting RNA (piRNA) and circular RNAs (circRNAs), has been observed to be involved in regulating the self‐renewal through forming an intricate regulatory network together with protein‐coding gene in different types of stem cells, including embryonic stem cells (ESC), induced pluripotent stem cells, cancer stem cells and adult stem cells including SSCs (S. Hu & Shan, ; Rosa & Ballarino, ; Wang et al, ; Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…GAS5 is the host gene of 11 human small nucleolar RNAs (snoRNA) involved in the 2'-O-methylation of rRNA. This lncRNA seems to be involved in embryogenesis, in fact, it increases OCT4, NANOG and SOX2 expression by Nodal regulation and is directly regulated by these stemness factors in hESCs, forming a circuit that promotes pluripotency (33). It has been demonstrated that ncRNAs are able to control different points of embryogenesis such asmaternal-zygotic transition, maintenance of pluripotencythe patterning of the body axes, specification and differentiation of cell types and organ morphogenesis (34).…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%